Labor Absorption Dynamics in the Furniture Industry: Development Furniture Business and Employment Opportunities - Victor F. F. D. Pasalbessy; Jemy Ricardo Parera (Journal of Business Management and Economic Development, 2026)
The furniture industry is one of the small and medium-sized industrial sectors that has significant potential in creating employment opportunities, especially in urban areas facing limited formal employment opportunities. In Jayapura City, the development of the furniture business has played a significant role in absorbing local labor, but this dynamic has taken place in an unstable situation due to fluctuations in market demand, limited capital, raw materials, and production technology. This study aims to analyze the dynamics of labor absorption in the furniture industry in Jayapura City, identify the factors that influence it, examine the strategies of business actors in increasing employment opportunities, and understand the relationship between the development of the furniture business and employment opportunities for the local community. This study uses a qualitative approach with a multiple-case study design. Data were collected through semi-structured in-depth interviews, field observations, and supporting documents from furniture business actors, workers, and related informants selected purposively. Data were analyzed using reflexive thematic analysis through the stages of coding, theme development, and meaning interpretation. The results show that labor absorption in the furniture industry in Jayapura City is fluctuating, not linear with business growth, and is greatly influenced by order-based production patterns. Local labor is an important potential, but still faces obstacles in terms of skills, discipline, and job sustainability. Amidst limited resources, business actors developed adaptive strategies through the use of core teams, project-based additional workers, informal training, product diversification, and utilization of customer social networks. These findings confirm that labor absorption in the furniture industry needs to be understood as a contextual socio-economic process, so that strengthening this sector requires support in terms of working capital, access to raw materials, skills development, and strengthening the local small business ecosystem. This study contributes to the literature on informal labor economics and small business development by offering a contextual understanding of employment dynamics in peripheral urban areas, while providing practical implications for local government policies aimed at promoting inclusive economic growth through the empowerment of small and medium-sized enterprises.